APLIKASI MOBILE BERBASIS ANDROID UNTUK PEMESANAN MAKANAN - Nunik Pratiwi; Rois Sovi Meitofa (UHAMKA Press, 2022)
Order errors are a problem that often occurs in restaurants that have many visitors. This happens because the process of recording orders is done manually, so that there are obstacles to the queue caused by stacks of paper that are not arranged according to the queue. This research designs and builds an Android-based mobile application that aims to reduce errors in the process of ordering food or drinks. The prototyping method is used in the system development process. Based on the results of black box testing, this ordering application can run well according to its function. In addition, system testing was also carried out on 25 respondents. The results obtained state that this application can be used properly and can help overcome the problem of order queues